Stress Driven Discovery of Natural Products From Actinobacteria with Anti-Oxidant and Cytotoxic Activities Including Docking and ADMET Properties - Syed Shams ul Hassan (MDPI AG, 2021)
Elicitation through abiotic stress, including chemical elicitors like heavy metals, is a new technique for drug discovery. In this research, the effect of heavy metals on actinobacteria Streptomyces sp. SH-1312 for secondary metabolite production, with strong pharmacological activity, along with pharmacokinetics profile, was firstly investigated. The optimum metal stress conditions consisted of actinobacteria strain Streptomyces sp. SH-1312 with addition of mix metals (Co2+ + Zn2+) ions at 0.5 mM in Gause’s medium. Under these conditions, the stress metabolite anhydromevalonolactone (MVL) was produced, which was absent in the normal culture of strain and other metals combinations. Furthermore, the stress metabolite was also evaluated for its anti-oxidant and cytotoxic activities. The compound exhibited remarkable anti-oxidant activities, recording the IC50 value of 19.65 ± 5.7 µg/mL in DPPH, IC50 of 15.49 ± 4.8 against NO free radicals, the IC50 value of 19.65 ± 5.22 µg/mL against scavenging ability, and IC50 value of 19.38 ± 7.11 µg/mL for iron chelation capacity and the cytotoxic activities against PC3 cell lines were recorded with IC50 values of 35.81 ± 4.2 µg/mL after 24 h, 23.29 ± 3.8 µg/mL at 48 h, and 16.25 ± 6.5 µg/mL after 72 h. Further mechanistic studies have revealed that the compound MVL has shown its pharmacological efficacy by upregulation of P53 and BAX while downregulation of BCL-2 expression, indicating that MVL is following apoptosis in varying degrees. To better understand the pharmacological properties of MVL, in this work, the absorption, distribution, metabolism, excretion, and toxicity (ADMET) were also evaluated. During ADMET predictions, MVL has displayed a safer profile in case of hepatotoxicity, cytochrome inhibition and also displayed as non-cardiotoxic. The compound MVL showed good binding energy in the molecular docking studies, and the results revealed that MVL bind in the active region of the target protein of P53 and BAX. This work triumphantly announced a prodigious effect of heavy metals on actinobacteria with fringe benefits as a key tool of MVL production with a strong pharmacological and pharmacokinetic profile.